Design and development of a photovoltaic (PV) system with a sun tracker - Chai, Koh Kiong. (Universiti Malaysia Sarawak (UNIMAS), 2010)
This thesis presents the design and implementation of solar photovoitaic (rV) system with a sun tracker. PVs are arrays of cells containing a solar photovoltaic material that convert radiation into direct current electricity via photovoltaic effect ts. installation of a sun tracker is one of the approaches to improve the performance ofa so lar photovoltaic system. A sun tracker is a device for orientating photovoltaic panel towards the sun. The aim of this paper is to examine the pelfolmance of a so lar photovoltaic system with a sun tracker in Batu Lintang, Kuching, Sarawak (I 0 (I 0 32'09.73 " N, Iloo 20'32. 70E). A designed and developed solar photovoltaic system that is equipped with a sun tracker is presented. The developed system consists of five modules, i.e. , a sensor system, a linear actuator system, a tracking mechanism, a battery storage system and charge controller, and a microcontroller system. Besides, the performance of the photo voltaic system with sun tracker and without sun tracker are compared, analyzed and evaluated with experiments. Concluding remarks is further presented.